Extended Performance Research on IEEE 802.11a WPA2 Multi-Node Laboratory Links - Carvalho, Jose Pacheco De (2022)
Wireless communications, involving electronicdevices, are increasingly important. Performance is a fundamental issue, leading to more reliable and efficient communications. Security is also, no doubt, most important. Laboratory measurements were achieved about several performance aspects of Wi-Fi IEEE 802.11a 54 Mbps WPA2 links. Our study enriches performance evaluation of this technology, using accessible equipments (HP V-M200 access points and Linksys WPC600N adapters). New accurate results are given, namely at OSI level 4, from TCP and UDP experiments. TCP throughput is measured against TCP packet length. Jitter and percentage datagram loss are evaluated versus UDP datagram size. Results are examined for point-to-point, point-to-multipoint and four-node point-to-multipoint links. Comparisons are also made mainly to related data obtained for Open links. Conclusions are extracted about performance of the links.